Escola-empresa: traços do empresário-sombra - Ada Beatriz Gallicchio Kroef; Gisele Soares Gallicchio (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This paper is a cartographic exercise in which we seek to highlight some traces, trajectories and lines that make up the always-changing contours of this machine called school. One of the transformations that is mapped here is concerned with the relationships and movements between the school in the business and the business in the school. These relationships engender mutations in the capitalistic flows that inform Societies of Control and constitute new situations and arrangements which contribute to give school its current shape.